Rituals, Runaways, and the Haitian Revolution Collective Action in the African Diaspora - Nicole Eddins, Crystal (Social Sciences, 2022)
The first scholar to focus on collective consciousness and resistance to enslavement before the Haitian Revolution, Eddins makes a major contribution to African Diaspora studies, sociology, history, and Latin American and Caribbean studies. This readable, theoretically grounded book provides essential context to understand the Haitian Revolution.